AI-Based Decision Support Systems in Project Management: Enhancing Efficiency and Accuracy - Obanor, Enoch I.; Adeodu, Adefemi O.; Ighrawve, Desmond E.; Nkwor, Jane C.; Richard, Onumajuru I. (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
Decision-making is vital for projects in project management to be completed successfully. Project managers have been using traditional decision support systems (DSS) for a long time; however, with artificial intelligence (AI), these systems are now much more powerful. This paper examines how using AI-based systems supports project managers to increase both efficiency and accuracy. Automating repetitive jobs, giving immediate data feedback, making resource decisions wisely and improving time control make AI-based DSS useful for project management. Such systems are more accurate in judging risks, modelling outcomes and monitoring activities which decreases human errors and results in more dependable project outcomes. Even though AI DSS clearly helps a lot, some problems such as reliable data, unifying different systems, ethics and its acceptance by users must still be overcome. It reviews scholarly literature, examines usable applications and discusses possibilities and ideas for the future, covering how AI-based DSS could change project management.